Rationalizing the binding and α subtype selectivity of synthesized imidazodiazepines and benzodiazepines at GABAA receptors by using molecular docking studies. (15th April 2022) - Golani, Lalit K; Yeunus Mian, Md; Ahmed, Taukir; Pandey, Kamal P; Mondal, Prithu; Sharmin, Dishary; Rezvanian, Sepideh; Witkin, Jeffrey M; Cook, James M
Graphical abstract: Abstract: The pharmacological actions exerted by benzodiazepines are dependent on the discrete α protein subunits of the γ-aminobutyric acid type A receptor (GABAA R). Recent developments via a cryo-EM structure of the α1β3γ2L GABAA R ion channel provide crucial insights into ligand efficacy and binding affinity at this subtype. We investigated the molecular interactions of diazepam and alprazolam bound GABAA R structures (6HUP and 6HUO) to determine key binding interaction domains. A halogen bond between the chlorine atoms of diazepam and alprazolam with the group on the backbone of the α1 histidine amino acid 102 is important to the positive allosteric modulatory actions of diazepam and alprazolam in the α1β3γ2L GABAA R ion channel. In order to gain insight into α subtype selectivity we designed and synthesized close structural analogs of diazepam and alprazolam. These compounds were then docked into the recently publish cryo-EM structures of GABAA Rs (6HUP and 6HUO). This modeling along with radio-ligand binding data resulted in the conclusion that the non-classical bioisosteric replacement of the chlorine atom at C7 with an ethinyl group (compound 5 ) resulted in an 11-fold gain in α5 binding selectivity over the α1 subtype. Moreover, the potency of compound 5 resulted in a ligand with less sedation than diazepam, while still maintaining the same anxiolytic potency. These modeling data extend our understanding of the structural requirements for α-subtype-selective compounds that can be utilized to achieve improved medical treatments. It is clear that the ethinyl group in place of a halogen atom decreases the affinity and efficacy of benzodiazepines and imidazodiazepines at α1 subtypes, which results in less sedation and ataxia.